Thickening agent for cyanoacrylate adhesive, method for producing same, and method for producing cyanoacrylate adhesive

By using a thickener of a specific particle size and general formula, the problem of the viscosity of the cyanoacrylate-based adhesive in storage is solved, and the stability and handling of the adhesive are improved.

CN119463737APending Publication Date: 2025-02-18ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411078353.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The viscosity of cyanoacrylate-based adhesives becomes higher in storage, and the prior art has failed to effectively solve the impact of thickeners on polymerization.

Method used

Use a bead-shaped methacrylic resin having an average particle size of 50 to 500 μm and a compound represented by a specific general formula as a thickening agent, and 0.01 to 10 mass % of the compound is contained with respect to 100 mass % of the methacrylic resin, and The stability of the thickener is ensured through drying and packaging processes.

Benefits of technology

The viscosity changes in storage of cyanoacrylate-based adhesives are effectively suppressed, and the storage stability of the adhesives are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463737A_ABST
    Figure CN119463737A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a thickener having little change in viscosity when used as a thickener for cyanoacrylate adhesives. The solution of the present invention is a thickening agent for a cyanoacrylate adhesive agent, the thickening agent for a cyanoacrylate adhesive agent comprising a methacrylic resin that is in the form of beads having an average particle diameter of 50-500 [mu] m and has a moisture content of 1% by mass or less and a compound represented by general formula (1), with respect to 100% by mass of the methacrylic resin, the amount of the compound represented by general formula (1) being less than or equal to 10% by mass, and the amount of the compound represented by general formula (1) being less than or equal to 10% by mass. Thickening agent for cyanoacrylate adhesives, said thickening agent containing 0.01-10 mass% of compound represented by general formula (1) # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thickener for a cyanoacrylate adhesive and a method for producing the same, and a method for producing the cyanoacrylate adhesive. Background Art

[0002] In the manufacture of coatings and adhesives, thickeners are used for the purpose of adjusting the viscosity of products to improve handling properties. Among thickeners, thickeners using methacrylic resin compositions have high transparency and weather resistance as transparent resins, and also have excellent affinity with adhesives such as alkyl cyanoacrylates and chemical resistance. Since methacrylic resin compositions quickly dissolve in monomers while maintaining transparency, they are widely used as thickeners for adhesives.

[0003] Among adhesives, cyanoacrylate adhesives are particularly used in a wide range of fields such as industrial, medical, and household use as instant adhesives because the alkyl cyanoacrylate as the main component has high anionic polymerizability and can be polymerized by weak anions such as a small amount of water or impurities, thereby firmly bonding various materials in a short time.

[0004] In addition, since cyanoacrylate adhesives have high polymerizability, an anionic polymerization inhibitor or a radical polymerization inhibitor is used to stabilize the viscosity.

[0005] However, cyanoacrylate adhesives that impart viscosity by dissolving methacrylic resins have a problem of failing to exhibit the expected polymerization inhibition ability due to the presence of anionic polymerization accelerators or radical polymerization accelerators derived from the methacrylic resins, and having a high viscosity during storage.

[0006] For example, Patent Document 1 discloses a cyanoacrylate adhesive containing various polymerization inhibitors.

[0007] For example, Patent Document 2 discloses a thickener containing a methacrylic resin which has excellent storage stability when exposed to 50° C. / 95% Rh conditions in methyl methacrylate.

[0008] For example, Patent Document 3 describes that a cyanoacrylate-based adhesive composition contains a polyalkyl (meth)acrylate having a weight average molecular weight of 200,000 or more as a thickener.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent document 1: Japanese Patent No. 3018859.

[0012] Patent document 2: Japanese Patent Application Publication No. 2018-178076.

[0013] Patent document 3: Japanese Patent Publication No. 4-15267. Summary of the invention

[0014] However, Patent Document 1 does not describe the influence of a thickener on polymerization.

[0015] In addition, Patent Document 2 provides a thickener having excellent long-term stability in methyl methacrylate by introducing a specific structure into the terminal of a resin, but does not describe viscosity stability in alkyl cyanoacrylate.

[0016] In addition, Patent Document 3 describes that a cyanoacrylate adhesive is formed by adding various stabilizers, but does not describe the influence of a thickener on polymerization.

[0017] Therefore, the present invention aims to provide a cyanoacrylate adhesive thickener that can be suitably used as an adhesive thickener, and particularly when used as a cyanoacrylate adhesive thickener, has little viscosity change due to polymerization and is excellent in storage stability.

[0018] Another object of the present invention is to provide a method for producing the thickener for a cyanoacrylate-based adhesive and a method for producing an adhesive containing the thickener for a cyanoacrylate-based adhesive.

[0019] The present inventors have made intensive studies to solve the above-mentioned problems and have surprisingly found that the viscosity change of a cyanoacrylate adhesive during storage can be suppressed by using a thickener for a cyanoacrylate adhesive, the thickener comprising a methacrylic resin in the form of beads having an average particle size of 50 to 500 μm and a water content of 1% by mass or less and a compound represented by the following general formula (1), wherein the thickener for a cyanoacrylate adhesive contains 0.01% by mass to 10% by mass of the compound represented by the following general formula (1) relative to 100% by mass of the methacrylic resin.

[0020]

[0021] [In the general formula (1), R1 represents a hydrogen atom, a methyl group or a tert-butyl group, and R2 and R3 each independently represent a hydrogen atom, a methyl group, a tert-butyl group, a hydroxyl group or a methoxy group. The total number of tert-butyl groups in R1, R2 and R3 is less than 2.]

[0022] That is, the present invention is as follows.

[0023] [1] A thickener for a cyanoacrylate adhesive, wherein the thickener for a cyanoacrylate adhesive comprises a methacrylic resin in the form of beads with an average particle size of 50 to 500 μm and a water content of 1% by mass or less, and a compound represented by the general formula (1), wherein the cyanoacrylate adhesive thickener contains 0.01% by mass to 10% by mass of the compound represented by the general formula (1) relative to 100% by mass of the methacrylic resin.

[0024] [2] The thickener for a cyanoacrylate adhesive according to [1], wherein the weight average molecular weight of the methacrylic resin is 85,000 or more and 5,000,000 or less.

[0025] [3] The thickener for a cyanoacrylate adhesive according to [1] or [2], wherein the compound represented by the general formula (1) is a powder at room temperature.

[0026] [4] The thickener for a cyanoacrylate adhesive according to any one of [1] to [3], wherein the compound represented by the general formula (1) contains two hydroxyl groups or contains one hydroxyl group and one methoxy group.

[0027] [5] A method for producing a thickener for a cyanoacrylate adhesive, which is a method for producing a thickener for a cyanoacrylate adhesive according to any one of [1] to [4], wherein the method comprises at least the following steps: a drying step of volatilizing the water content of the methacrylic resin; and a packaging step of packaging the methacrylic resin and the compound represented by the general formula (1) using a packaging material after the drying step.

[0028] [6] A package having a water vapor transmission rate of less than 1.0 g / (m 2 · 24h) The packaging material hermetically seals the thickener for a cyanoacrylate adhesive according to any one of [1] to [4].

[0029] [7] A method for producing a cyanoacrylate adhesive, wherein a methacrylic resin in the form of beads having an average particle size of 50 to 500 μm and a water content of 1% by mass or less is brought into contact with 0.01% by mass to 10% by mass of a compound represented by the general formula (1) relative to 100% by mass of the methacrylic resin, and then dissolved in the cyanoacrylate adhesive.

[0030] According to the present invention, when used as a thickener for a cyanoacrylate adhesive, a thickener capable of suppressing a change in the viscosity of the cyanoacrylate adhesive during storage can be provided.

[0031] In one embodiment of the present invention, the storage stability of the adhesive can be further improved by making the compound into a powder. Furthermore, in one embodiment of the present invention, the storage stability of the adhesive can be further improved by making the thickener into a package in a specific packaging state. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram showing an example of a method for producing the adhesive according to the present embodiment. DETAILED DESCRIPTION

[0033] Hereinafter, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail. The present invention is not limited to the following embodiment, and various modifications can be made within the scope of the gist of the invention.

[0034] [Thickener]

[0035] The thickener for cyanoacrylate adhesives of the present embodiment (hereinafter, sometimes simply referred to as "thickener") comprises a methacrylic resin in the form of beads with an average particle size of 50 to 500 μm and a water content of 1% by mass or less, and a compound represented by the following general formula (1), wherein the thickener for cyanoacrylate adhesives contains 0.01% by mass to 10% by mass of the compound represented by the general formula (1) relative to 100% by mass of the methacrylic resin.

[0036]

[0037] [In the general formula (1), R1 represents a hydrogen atom, a methyl group or a tert-butyl group, and R2 and R3 each independently represent a hydrogen atom, a methyl group, a tert-butyl group, a hydroxyl group or a methoxy group. The total number of tert-butyl groups in R1, R2 and R3 is less than 2.]

[0038] When the thickener for cyanoacrylate adhesives is used as a thickener for cyanoacrylate adhesives, it is possible to suppress changes in the viscosity of the cyanoacrylate adhesive during storage.

[0039] The thickener of this embodiment contains at least methacrylic resin. The thickener may contain only methacrylic resin as a resin component, or may contain methacrylic resin and other resins. In the thickener, the content of methacrylic resin is preferably 90% by mass or more. For the thickener, it is preferred that the resin component is only methacrylic resin. In addition, the thickener may contain one methacrylic resin alone, or may contain two or more in combination. In one example, it is more preferred that the thickener is composed of only a single methacrylic resin as a resin component.

[0040] The thickener of the present embodiment contains a compound represented by the above-mentioned general formula (1).

[0041] The thickener contains 0.01% to 10% by mass of the compound represented by the general formula (1) relative to 100% by mass of the methacrylic resin. From the viewpoint of suppressing the viscosity change in the thickener, the thickener preferably contains 0.03% by mass or more of the compound represented by the general formula (1). Another preferred range of the content of the compound represented by the general formula (1) is 0.05% by mass or more, and more preferably 0.08% by mass or more. In addition, from the viewpoint of suppressing the coloring caused by addition, the thickener preferably contains 8% by mass or less of the compound represented by the general formula (1). Another preferred range of the content of the compound represented by the general formula (1) is 5% by mass or less, 3% by mass or less, and more preferably 2% by mass or less. In addition, the compound represented by the general formula (1) may be used alone or in combination of two or more.

[0042] The thickener of the present embodiment can be suitably used as a thickener for cyanoacrylate-based adhesives.

[0043] It should be noted that, for cyanoacrylate adhesives, the bonding mechanism is based on anionic polymerization with water. Therefore, it can be considered that the compound represented by the above general formula (1) having free radical inhibition ability is not affected by the above-mentioned range of parts or types and does not affect the original bonding ability.

[0044] [Methacrylic resin]

[0045] In the present embodiment, the weight average molecular weight (Mw) of the methacrylic resin is preferably 85000 or more and 5000000 or less. The weight average molecular weight (Mw) of the methacrylic resin is more preferably 300000 or more and 5000000 or less because a small amount of the methacrylic resin can obtain a desired viscosity. If the amount added is too small, it will be affected by the deviation during weighing. Therefore, it is more preferably 300000 or more and 4000000 or less.

[0046] The methacrylic resin is in the form of beads having an average particle size of 50 to 500 μm. In terms of solubility in the cyanoacrylate adhesive, the average particle size of the methacrylic resin is more preferably 50 to 350 μm.

[0047] The moisture content of the methacrylic resin is 1% by mass or less, preferably 0.01% by mass or more and 1% by mass or less. If the moisture content of the methacrylic resin is to be suppressed to a lower level, it is sometimes necessary to dry for a long time. Therefore, from the viewpoint of productivity, the moisture content of the methacrylic resin is preferably 0.01% by mass or more. On the other hand, when the moisture content of the methacrylic resin is greater than 1% by mass, the storage stability after being dissolved in cyanoacrylates such as ethyl cyanoacrylate tends to deteriorate due to the influence of promoting anionic polymerization, and therefore, the moisture content of the methacrylic resin is preferably 1% by mass or less. The moisture content of the methacrylic resin is more preferably 0.01% by mass or more and 0.8% by mass or less, further preferably 0.02% by mass or more and 0.7% by mass or less, and most preferably greater than 0.03% by mass and less than 0.5% by mass.

[0048] In the present embodiment, as long as there is no special description, it is preferred that the methacrylic resin contains 80% by mass or more of methyl methacrylate monomeric units as monomeric units. In addition, the methacrylic resin may also contain alkyl acrylate monomeric units as monomeric units. From the viewpoint of suppressing the odor when dissolved in a certain substance (for example, when dissolved in alkyl cyanoacrylate), it is preferred that the methacrylic resin contains 90 to 99.9% by mass of methyl methacrylate monomeric units and 0.1 to 10% by mass of alkyl acrylate monomeric units. In addition, the methacrylic resin more preferably contains 95 to 99.8% by mass of methyl methacrylate monomeric units, further preferably contains 97 to 99.8% by mass, and particularly preferably contains 98 to 99.8% by mass. The methacrylic resin may contain other monomeric units except the methyl methacrylate monomeric units and the alkyl acrylate monomeric units, or may not contain them.

[0049] The methacrylic resin as described above can not only reduce the viscosity change but also suppress the odor when dissolved in a substance such as alkyl cyanoacrylate.

[0050] In the present embodiment, the mass ratio of the alkyl acrylate monomer unit is preferably 0.1 to 10% by mass relative to 100% by mass of the methacrylic resin. The mass ratio of the alkyl acrylate monomer unit is more preferably 0.2 to 5% by mass relative to 100% by mass of the methacrylic resin, further preferably 0.2 to 3% by mass, and particularly preferably 0.2 to 2% by mass. When the mass ratio of the alkyl acrylate monomer unit is 10% by mass or less relative to 100% by mass of the methacrylic resin, when dissolved in alkyl cyanoacrylate, etc., it is preferred that the specific odor caused by the residual alkyl acrylate monomer or impurities therefrom will not be generated. On the other hand, when the mass ratio of the alkyl acrylate monomer unit is 0.1% by mass or more relative to 100% by mass of the methacrylic resin, it is preferred that the odor improvement effect obtained by copolymerizing the alkyl acrylate monomer unit can be exerted.

[0051] The alkyl acrylate monomer unit preferably has an alkyl group having 4 or more carbon atoms. As the alkyl acrylate monomer unit having an alkyl group having 4 or more carbon atoms, it is preferred to use a monomer unit derived from an alkyl acrylate having an alkyl group having 4 to 8 carbon atoms, such as n-butyl acrylate, sec-butyl acrylate, and 2-ethylhexyl acrylate. From the viewpoint of reducing the odor of the cyanoacrylate solution of the methacrylic resin, the alkyl group of the alkyl acrylate monomer unit preferably has 4 to 8 carbon atoms. In addition, from the viewpoint of ease of availability and reduction of odor when dissolved in cyanoacrylate, the alkyl acrylate monomer unit is particularly preferably an n-butyl acrylate monomer unit.

[0052] The methacrylic resin may be composed only of a methyl methacrylate monomer unit and an alkyl acrylate monomer unit having an alkyl group having 4 or more carbon atoms, or may further contain other monomer units.

[0053] As the other monomer units, vinyl monomer units copolymerizable with methyl methacrylate can be mentioned, specifically, alkyl methacrylates having 2 to 18 carbon atoms in the alkyl group; alkyl acrylates having 1 to 3 carbon atoms in the alkyl group; α, β-unsaturated acids such as acrylic acid or methacrylic acid; acrylates containing aromatic groups such as benzyl acrylate; dicarboxylic acids containing unsaturated groups such as maleic acid, fumaric acid, itaconic acid and their alkyl esters; aromatic vinyl compounds such as styrene, α-methylstyrene, and styrene having substituents on the benzene ring; vinyl cyanides such as acrylonitrile and methacrylonitrile. base compounds; maleic anhydride, maleimide, N-substituted maleimide; esters obtained by esterifying the two terminal hydroxyl groups of ethylene glycol or its oligomers with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; esters obtained by esterifying the hydroxyl groups of two alcohols with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate; esters obtained by esterifying polyol derivatives such as trimethylolpropane and pentaerythritol with acrylic acid or methacrylic acid; polyfunctional monomers such as divinylbenzene, etc. These can be used alone or in combination of two or more. From the viewpoint of suppressing odor, when an alkyl acrylate having 1 to 3 carbon atoms in the alkyl group is contained, the mass ratio of the monomer units derived from the alkyl acrylate having 1 to 3 carbon atoms in the alkyl group relative to 100 mass % of all monomer units constituting the methacrylic resin is preferably less than 0.1 mass %, more preferably 0 mass %, that is, no monomer units derived from the alkyl acrylate having 1 to 3 carbon atoms in the alkyl group are contained.

[0054] In the present embodiment, other monomer units may be copolymerized within the range that does not impair the effects of the present invention. In consideration of solubility in cyanoacrylates and the like or odor when dissolved, when the total amount of methyl methacrylate and alkyl acrylate monomer units having an alkyl group with 4 or more carbon atoms is 100 parts by mass, the mass ratio of monomer units derived from other vinyl monomers copolymerizable with methyl methacrylate is preferably 0 to 20 parts by mass in 100 parts by mass of the methacrylic resin, more preferably 15 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less.

[0055] In 100 parts by mass of the methacrylic resin, the total mass ratio of the monomer units derived from methyl methacrylate and the alkyl acrylate monomer units having an alkyl group having 4 or more carbon atoms is preferably 80 parts by mass or more, more preferably 85 parts by mass or more, further preferably 90 parts by mass or more, further preferably 95 parts by mass or more, and particularly preferably 100 parts by mass.

[0056] [Compound represented by general formula (1)]

[0057] As described above, the thickener of the present embodiment contains a compound represented by the following general formula (1).

[0058]

[0059] In this embodiment, in the above general formula (1), R1 represents a hydrogen atom, a methyl group or a tert-butyl group, and R2 and R3 each independently represent a hydrogen atom, a methyl group, a tert-butyl group, a hydroxyl group or a methoxy group, wherein the total number of tert-butyl groups in R1, R2 and R3 is less than 2.

[0060] Furthermore, from the viewpoint of the effect of suppressing viscosity change, it is more preferred that the general formula (1) contains two hydroxyl groups, or contains one hydroxyl group and one methoxy group.

[0061] The form of the compound represented by the general formula (1) is not particularly specified, but is preferably solid at room temperature from the perspective of handling. As a more preferred form of the compound represented by the general formula (1), in order to uniformly mix with the methacrylic resin in the package, it is preferably a powder at room temperature in order to stably suppress the viscosity change when dissolved in the cyanoacrylate adhesive. If the compound represented by the general formula (1) is in the form of a powder, it has the effect of increasing the contact area and suppressing the free radical state or polymerization reaction of the methacrylic resin in the package through uniform mixing.

[0062] The method of adding the compound represented by the general formula (1) to the methacrylic resin is not limited. However, in order to suppress anionic polymerization of the cyanoacrylate adhesive, it is preferred to add the compound represented by the general formula (1) after a drying step to volatilize the water content of the methacrylic resin.

[0063] In the method for manufacturing a thickener for a cyanoacrylate adhesive of the present embodiment, it is preferred to include a packaging step of packaging the methacrylic resin and the compound represented by the general formula (1) with a packaging material. In addition, in the method for manufacturing a thickener for a cyanoacrylate adhesive of the present embodiment, it is preferred to include a drying step of volatilizing the water content of the methacrylic resin before the packaging step. It should be noted that, from the viewpoint of reducing the viscosity change, even if the methacrylic resin and the compound represented by the general formula (1) are not in the same package, there is no problem as long as they are in contact. That is, only the methacrylic resin can be packaged with a packaging material, and then the methacrylic resin can be brought into contact with the compound represented by the general formula (1).

[0064] When the methacrylic resin and the compound represented by the general formula (1) are packaged in the same package, the packaging material may be the following packaging container. As long as the methacrylic resin and the compound represented by the general formula (1) are in contact, the compound represented by the general formula (1) may be contained in the methacrylic resin, or the methacrylic resin and the compound represented by the general formula (1) may be dry-mixed and packaged. Preferably, the methacrylic resin and the compound represented by the general formula (1) are dry-mixed.

[0065] [Package]

[0066] The storage stability after being dissolved in cyanoacrylates such as ethyl cyanoacrylate has a tendency to be deteriorated by the influence of anionic polymerization promotion, and therefore, the packaging material used in the packaging is required to be substantially impermeable to water and can be sealed. As such packaging materials, for example, metal containers, cans, films on which metal aluminum is evaporated, polyethylene, etc. can be appropriately used. Before packaging the granular or beaded methacrylic resin, it is also a preferred method to replace the interior of the packaging container with a dehumidified gas or to package a hygroscopic material together to dehumidify.

[0067] More specifically, it is preferred that the packaging container (packaging material) has a water vapor transmission rate of less than 1.0 g / (m 2 That is, in one embodiment, it is preferred that the water vapor permeability is less than 1.0 g / (m 2 ·24h) of the material in which the cyanoacrylate adhesive is sealed with a thickener. Such a material includes metal materials such as iron, copper, steel, thin steel-tin-plated materials, and stainless steel materials with a film thickness of 10 μm or more; biaxially stretched polypropylene, polyvinylidene chloride films of polyethylene terephthalate films, aluminum vapor-deposited films, silicon dioxide vapor-deposited films, and biaxially stretched polypropylene films with a film thickness of 50 μm or more and a very low level of additives that may ooze out, etc. are used as the base material.

[0068] By packaging the thickener of the present embodiment with the above-described packaging material to form a package, the storage stability of the thickener can be further improved.

[0069] <Weight average molecular weight>

[0070] When the weight average molecular weight of the methacrylic resin is 1,800,000 or less, the weight average molecular weight of the methacrylic resin is measured by gel permeation chromatography (GPC), and when the weight average molecular weight of the methacrylic resin is greater than 1,800,000, it is measured by GPC-MALS.

[0071] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the methacrylic resin measured by gel permeation chromatography (GPC) is preferably 1.7 or more and 2.5 or less. From the viewpoint of ease of manufacture, Mw / Mn is more preferably 1.8 or more. In addition, from the viewpoint of suppressing the dissolution residue during dissolution and improving solubility, Mw / Mn is more preferably less than 2.5, further preferably less than 2.4, particularly preferably less than 2.3, and particularly preferably less than 2.3.

[0072] It should be noted that, for the weight average molecular weight Mw and number average molecular weight Mn measured by the above GPC, a standard methacrylic resin obtained as a reagent with a known monodisperse weight average molecular weight and an analytical gel column eluted from a high molecular weight component are used in advance, and a standard curve is prepared according to the elution time and the weight average molecular weight. The molecular weight of each sample can be determined from the standard curve. Specifically, it can be measured by the method described in the examples described below.

[0073] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the methacrylic resin measured by the above-mentioned GPC-MALS (Gel Permeation Chromatography-Multi-Angle Light Scattering) is preferably 1.0 or more and 3.0 or less. From the viewpoint of suppressing the dissolution residue when the cyanoacrylate is dissolved and improving the solubility, Mw / Mn is more preferably 1.0 or more and less than 2.3.

[0074] <Water content>

[0075] The moisture content of the methacrylic resin can be measured by the method described in the examples below, and is measured by a drying method. The drying method is a method in which 10.0 g of the methacrylic resin is kept at 70° C., and the measurement is completed when the weight loss rate in 10 seconds is 0.02% or less, and the total weight loss rate is taken as the moisture content.

[0076] The water content of the methacrylic resin (for example, methacrylic resin in the form of particles or beads) can be adjusted by, for example, a drying method of a slurry or the like after polymerization.

[0077] Examples of methods for drying the methacrylic resin include hot air drying in which hot air is sent from a hot air blower or a blower heater into a tank to dry the resin, vacuum drying in which the temperature is increased as necessary after reducing the pressure in the system, drum drying in which the obtained polymer is rotated in a container to fly out water, spin drying in which centrifugal force is used for drying, air flow drying in which the resin in a pipe is dried while being sent with hot air, and a fluidized bed dryer in which the bottom of the tank is opened and closed after drying at a specific temperature for a fixed time to allow the resin to fall into the next drying tank.

[0078] In order to make the moisture content within the above range, it is preferred that after the polymerization, the obtained slurry is dried with an air flow dryer and / or a fluidized bed dryer. In this case, since the final moisture content is significantly low, it takes time to process, so the productivity is poor, and in addition, problems such as poor pumping sometimes occur in the slurry liquid feeding process.

[0079] <Average particle size>

[0080] The average particle size refers to the volume average particle size. The volume average particle size can be measured by the method described in the examples described below.

[0081] The thickener of this embodiment is particularly used for cyanoacrylate adhesives. Here, the cyanoacrylate adhesive is preferably an adhesive containing an alkyl cyanoacrylate as a main component (for example, an adhesive containing 50% by mass or more of the alkyl cyanoacrylate relative to 100% by mass of the adhesive, more preferably 70% by mass or more).

[0082] Examples of the alkyl cyanoacrylate include cyanoacrylates having an alkyl group having 1 to 10 carbon atoms, such as methyl cyanoacrylate, ethyl cyanoacrylate, propyl cyanoacrylate, isopropyl cyanoacrylate, butyl cyanoacrylate, isobutyl cyanoacrylate, and octyl cyanoacrylate; methoxyethyl cyanoacrylate, ethoxyethyl cyanoacrylate, etc. Usually, ethyl cyanoacrylate is often used as the alkyl cyanoacrylate.

[0083] <Polymerization method>

[0084] The methacrylic resin can be produced using, for example, a monomer constituting the methacrylic resin, a polymerization initiator, a chain transfer agent, and other additives.

[0085] As a polymerization initiator, when free radical polymerization is used, di-tert-butyl peroxide, lauryl peroxide, dilauroyl peroxide, tert-butyl peroxy 2-ethylhexanoate, 1,1-bis(tert-butyl peroxide)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butyl peroxide)cyclohexane and other peroxide systems or azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile) and other azo systems, common free radical polymerization initiators can be used, and they can be used alone or in combination of two or more. These free radical initiators can also be combined with a suitable reducing agent and implemented as a redox system initiator.

[0086] In the case of suspension polymerization or emulsion polymerization, as a polymerization initiator, it is preferred to use a polymerization initiator having a 10-hour half-life temperature of less than 65° C. Specifically, dilauroyl peroxide is preferred.

[0087] The polymerization initiator is usually used in an amount within a range of 0.001 to 1% by mass based on 100% by mass of the total mass of the monomers.

[0088] In the method for producing the methacrylic resin, when producing by a radical polymerization method, a generally used chain transfer agent can be used to adjust the molecular weight.

[0089] As the chain transfer agent, for example, mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dimercaptoacetate, trimethylolpropane trimercaptoacetate, and pentaerythritol tetrakis(thioglycolate) are preferably used.

[0090] The chain transfer agent can be used in an amount within a range of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers. The amount of the chain transfer agent is determined based on the desired molecular weight.

[0091] As a polymerization method for methacrylic resin, suspension polymerization or emulsion polymerization is preferably used from the viewpoint of small particle size. In order to obtain granular resin beads in suspension polymerization and powdery resin beads in emulsion polymerization, it is advantageous in operation to dissolve an appropriate amount of a thickener for adjusting the slurry to a desired viscosity.

[0092] In addition, since the polymerization time of suspension polymerization is shorter than that of emulsion polymerization, suspension polymerization is preferred.

[0093] In particular, when the suspension polymerization method is used, it is preferred to make the molecular weight distribution within the above range. When it is required to suppress the generation of unmelted products due to the wide molecular weight distribution when dissolving in alkyl cyanoacrylates and the like at a high level and to maintain high storage stability after dissolution, it is preferred to obtain the product by a single-stage suspension polymerization rather than a multi-stage polymerization with a wide molecular weight distribution. If a two-stage polymerization is used, impurities from the suspending agent will increase, which is not preferred.

[0094] In addition, as a polymerization method of methacrylic resin, it is preferable to use a method of dispersing a suspending agent having an average particle size of 10 to 40 μm in water and polymerizing. Among them, it is preferable to disperse a suspending agent having an average particle size of 10 to 40 μm in water and perform a one-stage suspension polymerization.

[0095] In the method for producing methacrylic resin, it is preferred to perform polymerization with the average particle size of the suspending agent dispersed in the suspension polymerization water being 10 to 40 μm. This can control the standard deviation of the volume particle size of the methacrylic resin (e.g., methacrylic resin beads), stabilize the polymerization behavior, reduce the slow heating amount, and improve productivity.

[0096] The average particle size of the suspending agent can be adjusted by appropriately selecting the particle size of the suspending agent to be used. Furthermore, by mixing powders having different particle sizes, a suspending agent having an appropriate average particle size can be obtained.

[0097] In the method for producing a methacrylic resin, it is preferred that the pH of the aqueous phase be adjusted to a range of 4 to 7. By adjusting the pH to be within this range, the standard deviation of the particle diameter of the resin beads can be controlled and the polymerization behavior can be stabilized.

[0098] In the method for producing methacrylic resin, it is preferred that the suspending agent is heated to 50° C. to 90° C. before being added to water (50° C. to 90° C.) in the reactor. This allows the average particle size of the methacrylic resin (eg, methacrylic resin beads) and its variation to be adjusted.

[0099] According to the manufacturing method of methacrylic resin, inorganic suspending agents are more preferably used than organic suspending agents. This is because the residue of organic suspending agents makes it difficult to adjust the viscosity of cyanoacrylate adhesives. Here, as organic suspending agents, polyvinyl alcohol, methylcellulose, ethylcellulose, hydroxypropyl methylcellulose, carboxymethylcellulose, gelatin, polyvinyl acetate, etc. can be mentioned.

[0100] As the inorganic suspending agent, in view of the stability after dissolving in the alkyl cyanoacrylate, it is preferred to include an inorganic compound containing calcium and / or aluminum, for example, calcium phosphates such as tricalcium phosphate (third calcium phosphate), calcium carbonate, aluminum hydroxide and the like. In particular, from the viewpoint of stability after dissolving, the inorganic suspending agent is more preferably an inorganic suspending agent containing an inorganic compound containing aluminum.

[0101] The suspending agent may further contain a suspending aid such as polyethylene glycol, sodium ethylenediaminetetraacetate, sodium lauryl sulfate, etc. The suspending aid may be contained in an amount of 0.01 to 10% by mass relative to 100% by mass of the suspending agent.

[0102] It is preferred that the suspending agent is mixed in water together with the monomer raw material and used.

[0103] <Washing method>

[0104] In the method for producing methacrylic resin, acid washing, water washing, alkali washing, etc. are preferably performed to remove the suspending agent. The number of times these washing operations are performed can be selected optimally according to the operation efficiency and the removal efficiency of the suspending agent, and can be once or repeated multiple times.

[0105] The washing temperature may be selected optimally in consideration of the removal efficiency of the suspending agent and the degree of coloration of the obtained polymer, and is preferably 20 to 100° C. The washing temperature is more preferably 30 to 95° C., further preferably 40 to 95° C., and particularly preferably 50 to 80° C.

[0106] The washing time per washing is preferably 10 to 180 minutes, more preferably 20 to 150 minutes, from the viewpoints of washing efficiency, reduction of odor when used as a thickener, and solubility stability in cyanoacrylate.

[0107] The pH of the washing liquid used in washing can be within the range that can remove the suspending agent, and the preferred pH is 1 to 12. As for the pH during acid washing, from the perspective of the removal efficiency of the suspending agent or the color tone of the obtained polymer, the preferred pH is 1 to 5, and the more preferred pH is 1.2 to 4. As the acid used in acid washing, there is no particular regulation as long as it can remove the suspending agent, and conventionally known inorganic acids and organic acids can be used. An example of an acid preferably used is listed. As an inorganic acid, hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, boric acid, etc. can be cited, and a diluted solution diluted with water or the like can be used. As an organic acid, organic acids having a carboxyl group, a sulfonic group, a hydroxyl group, a thiol group, and an enol group can be cited. Considering the removal effect of the suspending agent or the color tone of the obtained resin, the acid used in acid washing is more preferably nitric acid, sulfuric acid, and an organic acid having a carboxyl group.

[0108] After the acid washing, it is preferred to further perform water washing or alkali washing from the viewpoint of suppressing the dissolution residue when dissolving in cyanoacrylate. A method of washing with warm water of 50°C or higher is more preferred, and a method of washing with warm water of 50°C or higher and then performing alkali washing and / or washing with warm water of 50°C or higher is further preferred.

[0109] By adjusting the pH of the slurry after washing to 2 or more and 9 or less, preferably 4 or more and 7 or less, more preferably 5 or more and 6.8 or less, and particularly preferably 5.5 or more and 6.5 or less, a thickener having excellent storage stability when dissolved in cyanoacrylate and excellent light resistance can be obtained.

[0110] [additive]

[0111] The thickener of the present embodiment may optionally contain other additives. The additives are not particularly limited as long as they can exert the effects of the present invention, and may be appropriately selected according to the purpose.

[0112] The additives include, but are not limited to, various stabilizers such as ultraviolet absorbers, heat stabilizers, and light stabilizers; plasticizers; flame retardants; flame retardant aids; curing agents; curing accelerators; antistatic agents; conductivity imparting agents; stress relaxants; mold release agents; crystallization accelerators; hydrolysis inhibitors; lubricants; impact imparting agents; slip improvers; compatibilizers; nucleating agents; reinforcing agents; flow regulators; dyes; sensitizers; colorants; anti-settling agents; anti-sagging agents; fillers; defoaming agents; light diffusing fine particles; rust inhibitors; antibacterial agents; antifungal agents; antifouling agents; conductive polymers, etc.

[0113] The thickener of the present embodiment may be the methacrylic resin obtained by the above method as it is and may be mixed with other methacrylic resin compositions to form a thickener.

[0114] The thickener of the present embodiment can be particularly suitably used as a cyanoacrylate (preferably alkyl cyanoacrylate, more preferably ethyl cyanoacrylate)-based thickener.

[0115] The mass ratio of the methacrylic acid resin in the thickener is preferably 80 to 90 mass %, more preferably 90 to 97 mass %, relative to 100 mass % of the thickener.

[0116] <pH of the aqueous phase when the thickener is dispersed in water>

[0117] For the thickener, after 20 g of the thickener and 100 g of pure water are dispersed by stirring, the mixture is allowed to stand, and the pH of the supernatant aqueous phase measured at room temperature after the solid content is settled is preferably 2 or more and 9 or less. From the viewpoint of maintaining a particularly good hue when the thickener is dissolved and used, solubility in cyanoacrylate, and suppressing odor from residual materials, the pH of the supernatant aqueous phase is more preferably 3 or more, and particularly preferably 3.5 or more. From the viewpoint of improving storage stability after dissolution in cyanoacrylate, etc., the pH of the supernatant aqueous phase is preferably 8.5 or less, more preferably 8 or less, and particularly preferably 7.5 or less.

[0118] <Water vapor transmission rate>

[0119] The water vapor transmission rate is “the amount of water vapor passing through a test piece per unit area per unit time under the conditions of a temperature of 40° C. and a humidity of 90% RH” and is measured by the cup method described in JIS Z 0208.

[0120] [Cyanoacrylate adhesive]

[0121] The present invention has also found that, by bringing a methacrylic resin into contact with a compound represented by the general formula (1) and then dissolving a thickener for a cyanoacrylate adhesive in the cyanoacrylate adhesive, the storage stability of the cyanoacrylate adhesive is improved compared to the case where a methacrylic resin and a compound represented by the general formula (1) are separately added to cyanoacrylate.

[0122] That is, one embodiment of the present invention is a method for producing a cyanoacrylate adhesive, wherein a methacrylic resin in the form of beads having an average particle size of 50 to 500 μm and a water content of 1% by mass or less is brought into contact with 0.01% by mass to 10% by mass of a compound represented by the general formula (1) relative to 100% by mass of the methacrylic resin, and then dissolved in the cyanoacrylate adhesive.

[0123] As described above, the cyanoacrylate-based adhesive produced by the above production method has more excellent storage stability.

[0124] The thickener of this embodiment is preferably used in a cyanoacrylate adhesive. Here, the cyanoacrylate adhesive preferably includes the thickener of this embodiment and cyanoacrylate (preferably alkyl cyanoacrylate). The cyanoacrylate adhesive may further contain an additive.

[0125] The viscosity ratio of the adhesive when stored at 70°C (viscosity at 25°C after 2 weeks at 70°C / initial viscosity at 25°C) is preferably 1.0 or more and less than 1.4. Here, the viscosity refers to a value measured with a vibration viscometer and can be measured by the method described in the Examples described below.

[0126] The viscosity ratio is more preferably 1.0 to 1.35, and even more preferably 1.0 to 1.3. When the viscosity ratio is within this range, an adhesive having stable handling properties can be obtained.

[0127] From the viewpoint of operation, the initial viscosity at 25° C. when the methacrylic resin is dissolved is preferably 0.5 to 2.0 Pa·s. As a specific concentration of the methacrylic resin, it is preferably dissolved in cyanoacrylate (preferably alkyl cyanoacrylate, more preferably ethyl cyanoacrylate) at 3 to 30% by mass, more preferably 4 to 25% by mass, and even more preferably 5 to 20% by mass, relative to 100% by mass of the adhesive.

[0128] The temperature at which the methacrylic resin is dissolved is preferably 30° C. or higher from the viewpoint of solubility, and is preferably 80° C. or lower from the viewpoint of stability.

[0129] Example

[0130] The present invention will be described in more detail using the following examples and comparative examples. It should be noted that the present invention is not limited to the following examples.

[0131] <Raw materials for methacrylic resins B-1 to B-3>

[0132] The raw materials used for preparing methacrylic resins B-1 to B-3 are as follows.

[0133] Methyl methacrylate (MMA): manufactured by Asahi Kasei Corporation (containing 2.5 mass ppm of 2,4-dimethyl-6-tert-butylphenol manufactured by Chugai Trade as a polymerization inhibitor).

[0134] Butyl acrylate (BA): manufactured by Toagosei Co., Ltd. (containing 15 mass ppm of 4-methoxyphenol as a polymerization inhibitor).

[0135] 2-Ethylhexyl thioglycolate (EHTG): manufactured by Arkema.

[0136] Dilauroyl peroxide (LPO): manufactured by NOF Corporation.

[0137] Ethylenediaminetetraacetic acid tetrasodium dihydrate (EDTA): manufactured by Kishida Chemical Co., Ltd.

[0138] Aluminum hydroxide: SBX73, B303, B153, and B103 manufactured by Nippon Light Metal Co., Ltd. were used (the average particle size was adjusted by appropriately mixing each).

[0139] [I. Production of methacrylic resin beads used as thickener]

[0140] (Example 1)

[0141] - Preparation of suspension concentrate -

[0142] 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 33 μm, 0.39 g of sodium lauryl sulfate and 2.3 g of EDTA were added to a container having a stirrer equipped with 4 inclined blades and mixed to obtain a mixed solution (a1). The average particle size of the suspending agent in the mixed solution (a1) was 33 μm, and the pH of the obtained mixed solution (a1) was 5.5. The obtained mixed solution (a1) was heated to 70°C.

[0143] -Polymerization reaction-

[0144] Then, 25 kg of water was added to a 60L reactor and the temperature was raised to 80°C, and 3 kg of the mixed solution (a1) and the monomer solution shown in Table 1 below were added to the reactor. Then, the suspension polymerization was carried out while maintaining a temperature of about 80°C, and an exothermic peak was observed 180 minutes after the monomer solution was added. Then, after the temperature was raised to 93°C at a rate of 1°C / min, the temperature was maintained at about 93°C for 45 minutes, and then the polymerization reaction was substantially terminated to obtain a polymer slurry. Then, the obtained polymer slurry was cooled to 50°C. In order to dissolve the suspending agent, 20% by mass of sulfuric acid was added to the polymer slurry to obtain a polymerization reaction solution. Next, the obtained polymerization reaction solution was passed through a 1.68 mm mesh sieve to remove the agglomerates, filtered, and separated into bead-like methacrylic resin particles and suspended waste liquid. The pH of the suspended waste liquid was 3.3.

[0145] -Washing process-

[0146] Then, bead-shaped methacrylic resin particles and approximately an equal amount of ion exchange water at about 70°C are added, and stirring, washing and filtering are carried out. Then, washing with ion exchange water at about 70°C is carried out again in the same manner (two water washings in total) to obtain a slurry polymer solution. An aqueous sodium hydroxide solution is dropped into the obtained slurry polymer solution to adjust the pH to 8.5, and stirring and washing are carried out. Then, the slurry polymer solution is filtered, and ion exchange water at 70°C is added, and stirring and washing are carried out. The pH of the obtained slurry polymer solution is 6.1. Then, the slurry polymer solution is filtered to obtain resin beads. The obtained resin beads are dried in an air flow dryer at 150°C under an air flow (30 Nm 3 / hr) and dried in a fluidized bed dryer (25 Nm 3 / hr) and dried at 90°C for 5 minutes to obtain methacrylic resin beads (B-1). For the obtained methacrylic resin beads (B-1), MMA:BA=99.5:0.5 (mass ratio), weight average molecular weight is 1600000, average particle size is 171μm, and moisture content is 0.2% by mass. Powdered 4-methoxyphenol (C-1) (trade name: MQ, solid (powder) under normal temperature conditions) (a compound represented by the general formula (1)) manufactured by Kawaguchi Chemical Industries, Ltd. was mixed with the obtained methacrylic resin beads in an amount shown in the following Table 2 to prepare a thickener, and the same package was formed. The packaging used an aluminum-containing packaging material (water vapor transmission rate: 0.8g / (m 2 / 24h)) and packaged by heat sealing.

[0147] (Examples 2 to 4, Comparative Example 2)

[0148] The same procedure as in Example 1 was carried out except that the number of parts of powdered 4-methoxyphenol (shown in Table 2 or Table 3 below) was changed.

[0149] (Comparative Example 1)

[0150] The same procedure as in Example 1 was carried out except that powdered 4-methoxyphenol was not added.

[0151] (Comparative Example 3)

[0152] The same procedure as in Comparative Example 2 was carried out except that the methacrylic resin beads and the powdered 4-methoxyphenol were not packaged together.

[0153] (Reference Examples 1 to 4)

[0154] The same procedures as in Examples 1 to 4 were carried out except that the methacrylic resin beads and the powdered 4-methoxyphenol were not packaged together.

[0155] (Examples 5 to 9)

[0156] The same procedure as in Example 2 was carried out except that another compound represented by the general formula (1) (C-2 to C-6 shown below) was used instead of the powdered 4-methoxyphenol (C-1).

[0157] C-2: 4-methoxyphenol (manufactured by Tokyo Chemical Industry Co., Ltd., solid at room temperature).

[0158] C-3: hydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd., solid at room temperature).

[0159] C-4: 6-tert-butyl-2,4-dimethylphenol (manufactured by Tokyo Chemical Industry Co., Ltd., liquid at room temperature).

[0160] C-5: tert-Butylhydroquinone (manufactured by Tokyo Chemical Industry Co., Ltd., solid at room temperature).

[0161] C-6: 4-tert-butylcatechol (manufactured by Tokyo Chemical Industry Co., Ltd., solid at room temperature).

[0162] (Examples 10 and 11)

[0163] The same procedure as in Example 2 was performed except that the monomer solution was set to the formulation shown in Table 1 below and was set to methacrylic resin (B-2) or (B-3). It should be noted that for methacrylic resin (B-2), MMA:BA=99.5:0.5 (mass ratio), weight average molecular weight was 450,000, average particle size was 350 μm, and water content was 0.2 mass %. In addition, for methacrylic resin (B-3), MMA:BA=99.5:0.5 (mass ratio), weight average molecular weight was 4,600,000, average particle size was 280 μm, and water content was 0.2 mass %.

[0164] Table 1

[0165]

[0166] (Reference Examples 5 to 8)

[0167] The same procedures as in Examples 5, 6, 8 and 9 were followed except that the methacrylic resin beads and the other compound represented by the general formula (1) were not packaged together.

[0168] (Comparative Example 4)

[0169] The same procedures as in Reference Examples 5 to 8 were carried out except that C-7 (2,6-di-tert-butylphenol manufactured by Tokyo Chemical Industry Co., Ltd., solid at room temperature) was used instead of the compounds represented by the general formula (1) (C-2 to C-5).

[0170] (Comparative Example 5)

[0171] The same procedure as in Comparative Example 4 was carried out except that the methacrylic resin beads and C-7 from Comparative Example 4 were packaged together.

[0172] (Comparative Example 6)

[0173] The same procedure as in Comparative Example 5 was carried out except that C-8 (2,6-di-tert-butyl-p-cresol manufactured by Tokyo Chemical Industry Co., Ltd., solid at room temperature) from Comparative Example 5 was used instead of C-7.

[0174] (Reference Example 9)

[0175] The same procedure as in Example 10 was followed except that C-1 (powdered 4-methoxyphenol) from Example 10 was not packaged in the same manner.

[0176] [II. Physical properties of methacrylic resin]

[0177] (II-1) (Weight average molecular weight)

[0178] The weight average molecular weights of the obtained methacrylic resin beads B-1 and B-2 were measured using the following apparatus and conditions.

[0179] Measuring apparatus: gel permeation chromatograph (HLC-8320GPC) manufactured by Tosoh Corporation, chromatographic columns: one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 connected in series in this order and used.

[0180] In this column, high molecular weight elutes quickly, while low molecular weight elutes later.

[0181] Detector: RI (differential refractometer) detector.

[0182] Detection sensitivity: 3.0mV / min.

[0183] Column temperature: 40°C.

[0184] Sample: 0.02 g of methacrylic acid resin in 20 mL of tetrahydrofuran.

[0185] Injection volume: 10 μL.

[0186] Developing solvent: tetrahydrofuran; flow rate: 0.6 mL / min. As an internal standard, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added.

[0187] As standard samples for calibration curve, the following 10 types of polymethyl methacrylates having known monodisperse peak top molecular weights and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.

[0188] Peak molecular weight (Mp) Standard reagent 1 1916000 Standard reagent 2 625500 Standard reagent 3 298900 Standard reagent 4 138600 Standard reagent 5 60150 Standard reagent 6 27600 Standard reagent 7 10290 Standard reagent 8 5000 Standard reagent 9 2810 Standard reagent 10 850

[0189] Under the above conditions, the RI detection intensity was measured with respect to the elution time of the methacrylic resin.

[0190] The weight average molecular weight (Mw) of the methacrylic resin was determined based on the area of ​​the region in the GPC elution curve and the calibration curve of the third-order approximation formula.

[0191] Since the molecular weight was too high in the above method, the weight average molecular weight of the methacrylic resin beads B-3 was measured under the following apparatus and conditions.

[0192] Measuring apparatus: Gel permeation chromatograph (HLC-8320GPC) manufactured by Tosoh Corporation.

[0193] Chromatographic column: Use 1 TSKguardcolumn H XL -H, 2 pieces of TSKgel GMH XL .

[0194] MALS:DAWN HELEOSII.

[0195] MALS laser wavelength: 659nm.

[0196] Eluent: THF (first grade product manufactured by Kishida Chemical Co., Ltd.).

[0197] Detection sensitivity: 3.0mV / min.

[0198] Column temperature: 40°C.

[0199] RI detector temperature: 40°C.

[0200] MALS temperature: room temperature.

[0201] Sample concentration: 0.5 mg / mL.

[0202] Injection volume: 100 μL.

[0203] (II-2) (Water content)

[0204] Using a Shimadzu moisture balance MOC-120H, 10.0 g of methacrylic resin beads were kept at 70°C. The measurement was completed when the weight loss rate in 10 seconds was 0.02% or less, and the total weight loss rate was taken as the moisture content.

[0205] (II-3) (Average particle size)

[0206] The average particle size was measured by the laser scattering method of LS13320 manufactured by Beckman Coulter, Inc. to obtain a volume average particle size (μm) of the methacrylic resin beads.

[0207] [III. Evaluation of thickener]

[0208] (III-1) (Storage stability at 70°C for 2 weeks)

[0209] like Figure 1 As shown in the upper section, Examples 1 to 11 and Comparative Examples 2, 5 and 6 of the same package are formed. Methacrylic resin and the compound represented by the general formula (1) are placed in a packaging container. In the same packaging state, they are placed at 50°C for 1 week. Then, the temperature is returned to room temperature, and the thickener is taken out and placed in a 30 mL screw bottle together with cyanoacrylate adhesive A (Alteco Co., Ltd., trade name "EE", viscosity: 3 mPa·s). The sample is shaken at 60°C for 2 hours with a constant temperature shaker (BR-23UM manufactured by TAITEC CORPORATION) to dissolve it. The dissolved sample is used as a test sample. Then, the storage stability test is carried out using the sample by the following method.

[0210] Comparative Example 1: In a state where only the methacrylic resin is packaged, it is placed at 50°C for 1 week, then returned to room temperature, the methacrylic resin is taken out, and put into a 30 mL screw bottle together with a cyanoacrylate adhesive A (manufactured by Alteco Co., Ltd., trade name "EE", viscosity: 3 mPa·s), and shaken at 60°C for 2 hours using a constant temperature shaker (BR-23UM manufactured by TAITEC CORPORATION) to dissolve it, and the dissolved sample is used as a test sample.

[0211] like Figure 1 As shown in the lower section, the comparative examples 3 to 4 and reference examples 1 to 9 added separately, only methacrylic resin was placed in a packaging container, and placed at 50°C for 1 week in a state where only methacrylic resin was packaged, then returned to room temperature, took out the methacrylic resin, and placed it in a 30mL screw bottle together with cyanoacrylate adhesive A (Alteco Co., Ltd., trade name "EE", viscosity: 3mPa·s) and compound C (compound represented by general formula 1), and was shaken at 60°C for 2 hours with a constant temperature oscillator (BR-23UM manufactured by TAITEC CORPORATION) to dissolve it, and the dissolved sample was used as a sample. Then, using this sample, a storage stability test was performed by the following method.

[0212] The viscosity η1 of the sample at 25°C was measured using a vibration viscometer VM-10A manufactured by Sekonic Corporation. The screw bottle was placed in an oven at 70°C in a sealed state for 2 weeks, then the screw bottle was taken out of the oven and the viscosity η2 of the sample at 25°C was measured. The viscosity ratio η2 / η1 when stored at 70°C for 2 weeks was taken as storage stability.

[0213] The storage stability when stored at 70°C for 2 weeks was evaluated as follows.

[0214] The viscosity ratio η2 / η1 is less than 1.3: A (very good).

[0215] The viscosity ratio η2 / η1 is 1.3 or more and less than 1.35: B (good).

[0216] The viscosity ratio η2 / η1 is 1.35 or more and less than 1.4:C (no problem).

[0217] The viscosity ratio η2 / η1 is 1.4 or more: D (poor).

[0218] (III-2) (Storage stability when adding another substance - Storage stability when packaged in the same manner)

[0219] The difference in viscosity ratio between methacrylic resin B and compound C represented by general formula (1) stored at 70°C for 2 weeks between the same packaging state and the different packaging state (addition separately) was calculated from the numerical values ​​described in the corresponding Examples, Reference Examples or Comparative Examples according to the following formula.

[0220] (Viscosity ratio when added separately) - (Viscosity ratio when packaged together)

[0221] The numerical values ​​in the examples were calculated as follows.

[0222] Example 1: (viscosity ratio of Reference Example 1) - (viscosity ratio of Example 1).

[0223] Example 2: (viscosity ratio of Reference Example 2) - (viscosity ratio of Example 2).

[0224] Example 3: (viscosity ratio of Reference Example 3) - (viscosity ratio of Example 3).

[0225] Example 4: (viscosity ratio of Reference Example 4) - (viscosity ratio of Example 4).

[0226] Example 5: (viscosity ratio of Reference Example 5) - (viscosity ratio of Example 5).

[0227] Example 6: (viscosity ratio of Reference Example 6) - (viscosity ratio of Example 6).

[0228] Example 8: (viscosity ratio of Reference Example 7) - (viscosity ratio of Example 8).

[0229] Example 9: (viscosity ratio of Reference Example 8) - (viscosity ratio of Example 9).

[0230] For example, Example 1 and Reference Example 1 differ only in the packaging state, and therefore (viscosity ratio of Reference Example 1) - (viscosity ratio of Example 1) is a positive number, indicating that the same packaging effect is achieved.

[0231]

[0232]

[0233] As can be seen from Tables 2 and 3, Examples 1 to 11 containing a methacrylic resin having a bead shape with an average particle size of 50 to 500 μm and a water content of 1 mass % or less and a compound represented by the general formula (1) have a relatively small viscosity ratio, and therefore have little viscosity change and are excellent in storage stability.

[0234] In addition, by comparing the storage stability when the same packaging is used and the storage stability when a separate addition is made, it can be seen that using the same packaging is effective.

[0235] According to the present invention, a thickener having excellent storage stability when used as a thickener for a cyanoacrylate-based adhesive can be provided.

Claims

1. A thickener for a cyanoacrylate adhesive, wherein: The thickener for a cyanoacrylate adhesive comprises a methacrylic resin in the form of beads with an average particle size of 50 to 500 μm and a water content of 1% by mass or less and a compound represented by the following general formula (1): The cyanoacrylate adhesive thickener contains 0.01% to 10% by mass of the compound represented by the general formula (1) based on 100% by mass of the methacrylic resin. In the general formula (1), R1 represents a hydrogen atom, a methyl group or a tert-butyl group, R2 and R3 each independently represent a hydrogen atom, a methyl group, a tert-butyl group, a hydroxyl group or a methoxy group, and the total number of tert-butyl groups in R1, R2 and R3 is less than 2.

2. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The weight average molecular weight of the methacrylic resin is 85,000 or more and 5,000,000 or less.

3. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The compound represented by the general formula (1) is a powder at room temperature.

4. The thickener for a cyanoacrylate adhesive according to claim 1, wherein The compound represented by the general formula (1) contains two hydroxyl groups or one hydroxyl group and one methoxy group.

5. A method for producing a thickener for a cyanoacrylate adhesive, which is a method for producing the thickener for a cyanoacrylate adhesive according to claim 1, wherein: The method comprises at least the following steps: A drying process, in which the water content of the methacrylic resin is volatilized; as well as A packaging step of packaging the methacrylic resin and the compound represented by the general formula (1) using a packaging material after the drying step.

6. A package, wherein: Use water vapor transmission rate less than 1.0g / (m 2 · 24h) is used to seal the thickener for a cyanoacrylate adhesive according to claim 1.

7. A method for producing a cyanoacrylate adhesive, wherein: A methacrylic resin in the form of beads having an average particle size of 50 to 500 μm and a water content of 1% by mass or less is brought into contact with 0.01% by mass to 10% by mass of a compound represented by the following general formula (1) based on 100% by mass of the methacrylic resin, and then dissolved in a cyanoacrylate adhesive. In the general formula (1), R1 represents a hydrogen atom, a methyl group or a tert-butyl group, R2 and R3 each independently represent a hydrogen atom, a methyl group, a tert-butyl group, a hydroxyl group or a methoxy group, and the total number of tert-butyl groups in R1, R2 and R3 is less than 2.

Citation Information

Patent Citations

  • Thickening of alpha-cyanoacrylate adhesive

    JP1992015267B2

  • Resin composition, thickener

    JP2018178076A